Adolescents’ Victim-Blaming Responses to Narratives About Sex Trafficking: Strategies for Curriculum Development - Hedrick McKenzie, Ashley (Violence against women, 2023)
In the United States, sex-trafficking awareness and prevention has increasingly become part of government-mandated health education. This exploratory study surveyed 250 U.S. adolescents to learn more about the use of media narratives in curricula about sex trafficking in light of research findings about victim-blaming responses to survivor narratives, as well as adolescents’ still-developing emotion-regulation skills. Victim blaming is counterproductive to the goals of trafficking awareness and prevention curricula. Participants viewed one of four narrative messages about a sex-trafficking victim/survivor. Over half of participants reported victim-blaming responses after viewing the message. Participants reported low perceived efficacy regarding the ability to recognize the signs of trafficking, and some participants experienced intense fear responses to the messages. Victim blaming was not associated with fear or perceived efficacy, contradicting predictions from the Extended Parallel Process Model. This study concludes with recommendations for educators and others tasked with communicating with adolescents about sex trafficking.